2008
DOI: 10.1680/coma.2008.161.3.97
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of demolition waste material

Abstract: Demolition waste materials, such as crushed concrete and bricks, have been utilised by the UK construction industry for applications such as the production of concrete, low level backfill and road subbase. There has been increased research on the properties of the recycled aggregates in the past decade but it mainly concentrates on the strength of these types of materials through shear box and triaxial tests.Little research has been undertaken on the physical properties of recycled materials, such as particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The low flakiness index value of NA can be explained by these materials being used in their natural state without being subjected to any crushing process, and the material becomes globular because of its geological formation resulting from wearing. Chidiroglou et al investigated the effect of RCA, which was subjected to second crushing, on the flatness index ( 97 ). Two types of crushing processes are applied.…”
Section: Properties Of Rcamentioning
confidence: 99%
See 1 more Smart Citation
“…The low flakiness index value of NA can be explained by these materials being used in their natural state without being subjected to any crushing process, and the material becomes globular because of its geological formation resulting from wearing. Chidiroglou et al investigated the effect of RCA, which was subjected to second crushing, on the flatness index ( 97 ). Two types of crushing processes are applied.…”
Section: Properties Of Rcamentioning
confidence: 99%
“…With the increase in the exposure time of the aggregates to the crushing process, the weak pieces break and the flat and elongated particles tend to become spherical. Thus, the amount of aggregate displayed as defective decreases ( 96 , 97 ).…”
Section: Properties Of Rcamentioning
confidence: 99%
“…One study in Hong Kong finds that the optimum moisture content got increased and the maximum dry density got decreased when the concrete aggregates were replaced by clay brick aggregates, which is mainly due to the low density and greater water absorption of bricks (Poon and Chan, 2006). Another study showed that the mechanical resistance showed improvement when sand (5%), cement (10%), and brick (6%) were added to recycled concrete aggregate (Chidiroglou et al, 2008). Experimental research work conducted on crushed concrete aggregates by Chidiroglou et al, 2008 suggested that different demolition waste materials are produced, which have different properties, and the results of the research would not be consistent with other wastes.…”
Section: Candd Materialsmentioning
confidence: 99%
“…Although there are a large number of studies focusing on the use of reclaimed asphalt slabs and crushed concrete aggregates in many geotechnical applications, limited research has been conducted on the use of bricks. An experimental study demonstrated the physical properties of demolition waste materials to reuse as fill materials for engineering purposes [37]. The researchers presented a study of the physical properties of three commercial types of cement and crushed bricks.…”
Section: Rubbles Of Clay Bricks In Mosulmentioning
confidence: 99%